Quality improvement process to assess tattoo alignment, set‐up accuracy and isocentre reproducibility in pelvic radiotherapy patients. Issue 4 (21st November 2014) - Elsner, Kelly; Francis, Kate; Hruby, George; Roderick, Stephanie
<x xml:space="preserve">Abstract</x> A prospective three cohort quality improvement study to improve set‐up accuracy for patients receiving pelvic radiotherapy without intraprostatic fiducial markers. Alignment of tattoos to minimise roll, yaw and pitch and defining cranio‐caudal (CC) isocentre position at the lateral tattoos improved set‐up accuracy and isocentre reproducibility.<boxed-text content-type="graphic" id="jmrs79-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>